Prostate volume, LUTS scale, and uroflowmetry of benign prostate hyperplasia patients with type 2 diabetes mellitus - A. N. Hakim; S. Soetojo; P. Lestari (Вестник урологии, 2024)
Introduction. Benign prostate hyperplasia (BPH) is an enlargement of the prostate due to abnormal proliferation or apoptosis failure of the epithelial or stroma tissues.Objective. To compare the prostate volume, IPSS score (LUTS scale), and uroflowmetry of BPH patients with type 2 diabetes mellitus.Materials & Methods. The medical records of BPH patients from 2011 to 2015 were assessed with an analytical retrospective study based on the prostate volume, IPSS score (LUTS scale), and Q max using uroflowmetry. The data were analyzed using the chi-square test by online statistical analysis.Results. Among 62 patients recorded, 11 patients were diabetic, while the rest were non-diabetic. No notable differences were observed between the two groups (p > 0.05) in prostate volume, IPSS score, and Q max.Conclusion. No significant differences in prostate volume, IPSS score (LUTS scale), and uroflowmetry between diabetic and non-diabetic BPH patients.